2005
DOI: 10.1016/j.apsusc.2004.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Study on ECR dry etching and selective MBE growth of AlGaN/GaN for fabrication of quantum nanostructures on GaN (0001) substrates

Abstract: This paper attempts to form AlGaN/GaN quantum wire (QWR) network structures on patterned GaN (0001) substrates by selective MBE growth. Substrate patterns were prepared along <112

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Following the success of growing GaAs-based [10] and InP-based [11] nanowires by our selective molecular beam epitaxy (MBE) growth on patterned substrates [13], we have recently succeeded in growing positionand size-controlled AlGaN/GaN nanowire network structures on (0001) pre-patterned GaN substrates by our selective MBE growth method [47,48].…”
Section: Selective Mbe Growth Of Gan Nanowire Network and Heterointementioning
confidence: 99%
“…Following the success of growing GaAs-based [10] and InP-based [11] nanowires by our selective molecular beam epitaxy (MBE) growth on patterned substrates [13], we have recently succeeded in growing positionand size-controlled AlGaN/GaN nanowire network structures on (0001) pre-patterned GaN substrates by our selective MBE growth method [47,48].…”
Section: Selective Mbe Growth Of Gan Nanowire Network and Heterointementioning
confidence: 99%
“…AlN, GaN, and Al x Ga 1 À x N) within them. Many studies have sought to exploit the growth control achieved in mature thin film deposition techniques, such as metal-organic chemical vapour deposition (MOCVD) [2,7] and molecular beam epitaxy (MBE) [1,5,[8][9][10][11][12][13][14], for the growth of 1D GaN-based nanostructures. GaN columnar growth by MBE has been demonstrated directly on Si [15] and on sapphire substrates using either AlN and GaN buffer layers [5,13] or catalyst seeds [1].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum wire width was below 10 nm, and the maximum amount of blueshift of the photoluminescence ͑PL͒ peak energy due to quantum confinement was 440 meV, including a significant contribution from lateral confinement. As for the GaN-based wires, 14,15 it has shown that the growth of the wire below 40 nm could be possible on ͗11-20͘-oriented mesas patterned on ͑0001͒ substrates. Such selective grown wires have the great advantage for the planar integration of quantum devices due to the good controllability of their position as compared with the free-standing nanowires or nanocolumns.…”
Section: Introductionmentioning
confidence: 99%